Philippine union catalog. Jan. - Mar. 1974. (Quezon City : University of the Philippines Library, 1974)
Issued quarterly Jan-Mar, Ap-Je, Jl-Sept and in annual cumulations. Supersedes Philippine bibliography and the Filipiniana union catalog. " Comp. by the University of the Philippines Library."